Tingkat Adopsi Alsintan Modern dan Tantangan Modernisasi Pertanian Indonesia Berdasarkan Sensus Pertanian 2003,2013, dan 2023 - Nofa Putri Amelia; Syarif Imam Hidayat; Ika Sari Tondang (SAFE-Network, 2026)
Agricultural modernization through the use of agricultural tools and machinery became one of the important pathways to improve farm efficiency, especially as Indonesia’s agricultural sector faced pressures from land conversion, an aging farming population, and the weak regeneration of agricultural labor. This article aimed to analyze the level of modern agricultural machinery adoption among Agricultural Business Households (RTUP) in Indonesia and to interpret the challenges of agricultural modernization based on the Agricultural Census data from 2003, 2013, and 2023. This study used a descriptive-comparative quantitative approach by relying on secondary data from publications of Statistics Indonesia, policy documents, and related scientific articles. The analysis was carried out through data tabulation, percentage change calculations, growth rate analysis, and interpretation of factors that hindered technology adoption. The findings showed that the number of RTUP declined from 31.23 million in 2003 to 26.14 million in 2013, before increasing to 28.42 million in 2023. At the same time, the use of modern technology among farmers/RTUP in 2023 only reached around 46.84%, indicating that more than half of agricultural business actors had not been adequately reached by modernization. The low adoption of agricultural machinery was associated with the dominance of older farmers, limited land ownership, lack of capital, low digital literacy, limited infrastructure access, and uneven extension services and machinery assistance. These findings indicated that agricultural modernization could not rely merely on the distribution of machinery, but also required institutional strengthening, operator training, financing schemes, and strategies to encourage the regeneration of young farmers.